Jalan Ditutup, Suara Dibuka: Boikot Jalan sebagai Ekspresi Ketidakadilan Sosial di Bima - Wahyudi Wahyudi; Herman Herman (Universitas Hamzanwadi, 2026)
This study aims to examine the practice of road blockades in Bima Regency as a manifestation of grassroots social movements responding to social injustice, particularly those related to deteriorating road infrastructure, weak security protection, and limited formal mechanisms of participation. Road blockades are not viewed merely as disruptions to public order; rather, they are understood as collective political tactics employed by citizens to pressure the state into addressing their demands. This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews with community members and relevant actors, direct field observations at road blockade sites, and document analysis of media reports and official government records. The data were analyzed thematically, drawing on perspectives from political sociology and social movement theory. The findings indicate that road blockades in Bima represent an accumulation of structural grievances stemming from prolonged road deterioration, rising levels of criminal activity, and the slow response of local government authorities. Road infrastructure, as a form of public space, has undergone a process of politicization and has been transformed into an arena for collective expression in the pursuit of social justice. For local residents, road blockades are perceived as a means of reclaiming bargaining power within an unequal relationship of power vis-à-vis the state. Meanwhile, governmental responses to these actions are ambivalent, oscillating between mild repressive measures and dialogical approaches, with policy implementation remaining partial and inconsistent. These findings underscore that road blockades constitute a rational and context-specific repertoire of local collective action, while simultaneously reflecting weaknesses in public service governance in marginalized regions such as Bima.